Non-invasive therapeutic drug monitoring: LC-MS validation for lamotrigine quantification in dried blood spot and oral fluid/saliva - Pelcová, Marta; Ďurčová, Viktória; Šmak, Pavel; Strýček, Ondřej; Štolcová, Miriam; Peš, Ondřej; Glatz, Zdeněk; Šištík, Pavel; Juřica, Jan (Journal of pharmaceutical and biomedical analysis, 2025)
Epilepsy, affecting over 50 million people globally, presents a significant neurological challenge. Effective prevention of epileptic seizures relies on proper administration and monitoring of Anti-Seizure Medication (ASMs). Therapeutic Drug Monitoring (TDM) ensures optimal dosage adjustment, minimizing adverse effects and potential drug interactions. While traditional venous blood collection for TDM may be stressful, emerging alternative sampling methods, particularly Dried Blood Spot (DBS) or oral fluid offer less invasive way of sampling. This study aimed to develop and validate an analytical method for the determination of lamotrigine in such alternative samples. The sample, either DBS or oral fluid, was subjected to extraction, evaporation, and reconstitution in 15 % acetonitrile containing 0.1 % formic acid. A Kinetex C18 Polar column was used for liquid chromatographic separation and MS in ESI+ mode was used for detection and quantitation of lamotrigine using an isotopically labelled internal standard according to EMA guidelines. The calibration range of the developed method enables the determination of lamotrigine in the concentration range of 1-30 μg/mL in DBS and 0.5-20 μg/mL in oral fluid. Oral fluid and DBS samples from patients treated with lamotrigine analysed by the developed method were compared to plasma concentrations measured by the hospital's accredited laboratory. Preliminary results indicate a promising potential for these alternative matrices in clinical TDM applications. By offering a less invasive sampling approach, this method improves the accessibility and safety of pharmacotherapy for epilepsy patients. The results of this study lay the foundation for further clinical applications by implementing alternative matrix TDM, which may significantly advance personalized care in epilepsy management.
Keywords: Alternative matrix; Chromatography, Liquid; Drug Monitoring; Saliva; test suché kapky krve; tandemová hmotnostní spektrometrie; Quantification; Validation; kalibrace; reprodukovatelnost výsledků; Anticonvulsants; chromatografie kapalinová; epilepsie; Reproducibility of Results; limita detekce; kapalinová chromatografie-hmotnostní spektrometrie; lidé; Liquid Chromatography-Mass Spectrometry; Dried Blood Spot Testing; Humans; lamotrigin; monitorování léčiv; Dried blood spot; antikonvulziva; Limit of Detection; sliny; Lamotrigine; Tandem Mass Spectrometry; Epilepsy; Calibration; Antiepileptics